Evaluating Disaster Management Policies from a Public Administration Perspective: A Systematic Literature Review - Kurhayadi (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This study examines disaster management policies through the lens of public administration by synthesizing insights from the existing scholarly literature. Using a structured literature review approach, the article systematically analyzes peer-reviewed studies on disaster management policies published in international journals. The review focuses on how administrative capacity, institutional arrangements, and governance mechanisms shape the effectiveness of disaster management policies. The findings indicate that policy outcomes are strongly influenced by coordination across government levels, inter-organizational collaboration, and the clarity of administrative roles and responsibilities. The literature also reveals persistent challenges related to fragmented governance structures, limited bureaucratic capacity, and weak accountability mechanisms. From a public administration perspective, disaster management policies are not merely technical instruments but reflections of broader administrative and political systems. The synthesis highlights that adaptive governance and institutional learning are critical for improving policy resilience in disaster contexts. The review identifies gaps in the integration of public administration theories within disaster management research. This study contributes to the literature by offering a comprehensive administrative framework for evaluating disaster management policies. The findings provide theoretical and practical implications for scholars and policymakers seeking to strengthen disaster governance through improved public administration practices.